La soutenabilité de l’accumulation du capital et de ses régimes. Une approche macroéconomique en termes de soutenabilité forte - Louison Cahen-Fourot (Revue de la Régulation)
The subject of my PhD is The sustainability of capital accumulation and its regimes: a strong sustainability macroeconomic approach. It is composed of two parts. The first one is composed of two chapters that review the literature on two aspects: The first chapter tackles the debate on stationary capitalism. It reviews the way capitalism is taken into account by ecological economists and analyzes it in light of historical examples of ecological crises and of insights from eco-marxist theories. Chapter 2 tackles the debate about the so-called monetary growth imperative analysed from a post-Keynesian point of view. The second part is a more empirical one and is composed of three chapters. Chapter 3 attempts at framing the exergy-useful work approach into a régulationnist theoretical framework informed with insights from the Carbon democracy approach. It investigates the social relationship to energy in the Fordist and Neoliberal accumulation regimes. The fourth chapter attempts at furthering the third chapter by investigating the CO2 - GDP relationship through econometric means taking into account structural breaks between accumulation regimes and possible asymmetries. Chapter 5 investigates the commitment of countries to reduce their greenhouse gas emissions within the context of globalized finance-led capitalism.